Pimozide cf. Haloperidol in Tourette Syndrome - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1997)
Pimozide (3.4 mg/day) and haloperidol (3.5 mg/day) therapy for Tourette syndrome were compared in a double-blind, 24-week, placebo-controlled crossover study of 22 patients, aged 7-16 years, at the Institute of Psychiatry, Charleston, SC.